KEPUASAN SEBAGAI VARIABEL MEDIASI KUALITAS PELAYANAN, KOMUNIKASI PEMASARAN DAN PENANGANAN KELUHAN TERHADAP LOYALITAS - Sintia, Ina; Mismiwati, Mismiwati; Zahrani, Syamsiar; Krisdayanti, Helisia; Riduwansah, Riduwansah (I-Economics, 2024)
This research aims to determine the influence of service quality, marketing communications and complaint handling on customer loyalty with customer satisfaction as a mediating variable at Bank Sumsel Babel Syariah Palembang. The population of this research is all customers of Bank Sumsel Babel Syariah Palembang. The sampling technique uses the formula Hair et al. The survey used a questionnaire conducted on 110 customers. Data analysis using Smart PLS 4.0. The research results show that service quality, marketing communication and complaint handling have a positive and significant effect on customer satisfaction, service quality, marketing communication and complaint handling have a positive and significant effect on customer loyalty. Service quality does not have a positive and significant effect on loyalty with satisfaction as a mediating variable , meaning that customer satisfaction is unable to mediate the influence of service quality on customer loyalty. Marketing communication and complaint handling have a positive and significant effect on customer loyalty with customer satisfaction as a mediating variable, meaning that customer satisfaction is able to mediate marketing communication and complaint handling on customer loyalty at Bank Sumsel Babel Syariah Palembang